Chronic endometritis at present: focus on overcoming implantation failures - Mekan R. Orazov; Viktor E. Radzinsky; Evgeny D. Dolgov (LLC "MEDIAFORMAT", 2024)
Chronic endometritis "from pathogenesis to therapy" still remains the most contrarian issue of modern gynaecology. The lack of a unified pathogenetic concept as well as diagnostic and therapeutic algorithms continue to support a multitude of scientific discussions around this unique nosology. Latent subclinical endometrial inflammatory changes are associated with the realization of reproductive failures, including repeated implantation failures and early reproductive losses. To date, a sufficient amount of scientific data has been accumulated demonstrating high efficacy and safety of antifibrotic therapy with the use of azoximer bovgialuronidase (Longidaza) in the complex treatment of chronic endometritis.